Bilibid growing up beneath prison walls - Virtusio, Romeo P. (San Juan City Published and exclusively distributed by Context Innovators & Resources International., 2009)
A memoir of the author's childhood in Bilibid, the national prison in the Philippines, where his father worked for decades as an employee and minor official.
College Student
In English.